The behaviour of a water droplet in a flow field of natural convection in a cubic enclosure with magnetic field. (6th April 2005) - Wang, Xian; Tagawa, Toshio; Ozoe, Hiroyuki; Hirano, Hiroyuki; Wang, Qiuwang
The behaviour of a water droplet was numerically studied in natural and magnetic convection of air. The magnetic field was computed using Biot-Savart's law. The Newton's equation of motion was solved for a particle and the Stokes' law of resistance was taken into account for the drag force. The results show that the magnetic field enhances the natural convection of air in the cubical cavity greatly. The influence of the flow field on the motion of a particle increases with the increase in the Ra number. The influence of the magnetic field on the particle increases with the increase in γ which represents the strength of the magnetic field. A particle is levitated in the combined field at larger γ. The initial position of a particle affects its behaviour and its final position. The final position does not depend on the initial velocity if it is not too high.